COVID-19 pandemisinin el cerrahisi üzerine etkisi Impact of COVID-19 pandemic on hand injuries - ÇAVUŞ ÖZKAN, MELEKBER; SARAÇ, ÖMER; KESİMER, MEHMET DENİZ; DURMUŞ KOCAASLAN, FATMA NİHAL; SAÇAK, BÜLENT; AKDENİZ DOĞAN, ZEYNEP DENİZ (My University, 2022)
BACKGROUND: The aim of the study was to evaluate etiologies of hand injuries in emergency department (ED), to compare the etiologies of hand injuries at the time of this study with the previous year, to assess whether novel coronavirus-2019 (COVID-19) pandemic affected the treatment decisions, and to investigate the COVID-19 infection rate within the first 14 days after admission. METHODS: A total of 229 patients admitted to ED with hand injury between March 15 and April 30, 2020, were included in the study. The control group consisted of 439 ED admissions with hand injury in the previous year (March 15-April 30, 2019). Data including age, sex, cause of trauma, treatment, and COVID-19 infection status within 14 days after ED admission were compared between groups. RESULTS: The mean age was 32.30±15.63 years in the study group and 30.85±18.54 years in the control group. The number of patients consulted to the surgery department decreased by 52.6% and the number of patients admitted to ED with hand injuries de-creased by 47.6% during the pandemic, compared to the previous year (p=0.0001). The incidence of home accidents increased and the glass cuts and penetrating/perforating injuries were the most common causes during the pandemic most of which occurred at home. CONCLUSION: The COVID-19 pandemic-mandated social restrictions led to a significant decrease in the number of ED admissions with hand injuries and the type of injuries. The incidence of home accidents increased with more time spent indoors. This study may be a useful guide for ED admissions of hand injury cases and management planning in the current and future pandemics.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Acil Tıp; Anesteziyoloji; Medicine; Health Sciences; Surgery Medicine Sciences; Emergency Medicine; Anesthesiology; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; ANESTEZİYOLOJİ; ACİL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; ANESTHESIOLOGY; EMERGENCY MEDICINE; Cerrahi; Anesteziyoloji ve Ağrı Tıbbı; Surgery; Anesthesiology and Pain Medicine; COVID-19; emergency department; hand injury; hand surgery; pandemic; TRAUMA; LOCKDOWN; WORK